2013
DOI: 10.1021/am4004683
|View full text |Cite
|
Sign up to set email alerts
|

Scab-Inspired Cytophilic Membrane of Anisotropic Nanofibers for Rapid Wound Healing

Abstract: This work investigates the influence of cytophilic and anisotropic nanomaterials on accelerated cell attachment and directional migration toward rapid wound healing. Inspired by the anisotropic protein nanofibers in scab, a polyurethane (PU) nanofibrous membrane with an aligned structure was fabricated. The membrane showed good affinity for wound-healing-related cells and could guide cell migration in the direction of PU nanofibers. Also, the morphology and distribution of F-actin and paxillin of attached cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Recently, nanomaterials have been widely used for biological applications, 6,7 such as drug delivery vehicle, 8 regenerative medicine and tissue engineering. [9][10][11][12] Due to the remarkable features of nanostructures, nanomaterials are able to affect cell morphology, 13,14 adhesion, [15][16][17] polarization, 18 differentiation [19][20][21] and lineage commitment. 22,23 Furthermore, nanostructures have been conrmed to inuence molecule transport, 24 cell signaling in response to soluble factors and mechanotransduction.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, nanomaterials have been widely used for biological applications, 6,7 such as drug delivery vehicle, 8 regenerative medicine and tissue engineering. [9][10][11][12] Due to the remarkable features of nanostructures, nanomaterials are able to affect cell morphology, 13,14 adhesion, [15][16][17] polarization, 18 differentiation [19][20][21] and lineage commitment. 22,23 Furthermore, nanostructures have been conrmed to inuence molecule transport, 24 cell signaling in response to soluble factors and mechanotransduction.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the nutrient minerals required for human body includes cobalt in a very minute traces that act as a cofactor for the synthesis of biomacromolecules to regulate the system. Hence, it was believed that the early release of curcumin reduced inflammation and pathogenic response during first 6 days of inflammatory phase, and the progression of proliferative phase was regulated by marginal release of curcumin and strategic release of cobalt nanoparticle which influenced cell-proliferation, collagen deposition, angiogenesis, scar formation, and re-epithelialization. The nanotherapeutics-loaded nanofibrous scaffolds can be used as a promising wound dressing material for tissue-engineering applications. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…Self-assembled peptide nanofiber scaffolds such as IKVAV YIGSR RGDS PHSRN DGEA and electrospun such as polyurethane have also been utilized in lens regeneration (Nibourg et al, 2016). Given the regenerative capacity of lens epithelial progenitor cells and pigmented epithelial cells of the dorsal iris, the lens can be restored when these nanoscaffolds are injected into the lens capsule after removing its contents (Xi et al, 2013).…”
Section: Nanoparticles For Biocompatible Scaffoldsmentioning
confidence: 99%